Evaluation of energy efficiency potentials from generator operations on vessels - Yigit, Kenan (PERGAMON-ELSEVIER SCIENCE LTD, 2022)
This paper presents the energy efficiency potentials from Diesel generator operations on bulk carrier, chemical tanker, ro-ro, and container vessels. The electrical energy usage that may occur if the generators are operated in the range of 40%-90% capacity was examined in terms of annual average fuel consumption, fuel cost, and emissions. In this study, the type and size of vessels, generator specifications, electrical energy demand, and time spent at berth, maneuvering, and at sea were considered. Thus, the annual energy savings obtained from various load sharing practices of generators were analyzed. The results showed that although annual savings vary according to the type of vessel, a minimum of 7% reduction in fuel consumption, fuel costs, CO2, and NOx emissions can be achieved if generators are operated at 90% instead of 40% capacity. The minimum reduction in SOx is also around 5%. In addition, it is possible to achieve savings of up to 17% in all parameters. Therefore, marine generators should be set to their optimum capacity to help reduce energy use and emissions from shipping. In this context, some predictive methods or alternative energy sources can be integrated into the main switchboard to keep the generators at their optimum capacity. (c) 2022 Elsevier Ltd. All rights reserved.
Keywords: Shipping; Marine electricity; Generator set; Energy use; Energy ef ficiency; SYSTEMS; Thermodynamics; Energy & Fuels